Análise das propriedades mecânicas e da biocompatibilidade de cimentos ortodônticos modificados por clorexidina - Sampaio, Gêisa Aiane de Morais (2015)
The aim of this study was to evaluate the mechanical properties and biocompatibility of orthodontic GICs with the addition of chlorhexidine digluconate (CX) in 10% and 18% concentrations. The materials were divided into seven groups (n = 12): C (control, Polyethylene), M (Meron Control), M10 (Meron, CX10%), M18 (Meron, CX18%), KC (Ketac Cem Control), KC10 (Ketac CX10%) and KC18 (Ketac CX18%). For biological analysis were used 84 Wistar rats, the cements were inserted into the subcutaneous tissue of rats and biopsies taken after 7, 15 and 30 days. Tissue samples were analyzed morphologically for the presence of inflammatory cellular events (inflammatory infiltrate, edema, necrosis, granulation tissue, giant cells, young fibroblasts and collagen fibers) and immunohistochemical analysis (IH) as the amount of CD68+ cells. Resistance analyzes the diametrical traction (DT), compression (CR) and Shear Bond Strength (SBS) were performed through an universal machine. After completion of the shear strength test, the labial surface of each specimen was evaluated in stereoscopic magnifying glass to quantify the Remnant Index Sticker (RIS). Vickers Microhardness tests were performed using 200g load over 15s. For the morphological and immunohistochemical evaluations were used the nonparametric Kruskal-Wallis and Dunn's test (P<0.05). For evaluation of mechanical properties was used one-way ANOVA followed by multiple comparison test of Tukey (P<0.05). The morphological study of tissues, had inflammatory infiltrated with significant difference between the groups C and KC18 at 7 (P=0.013) and 15 (P=0.032) days. Granulation tissue showed a significant difference between the groups C and M18 (P=0.029), with 7 days. Giant cells (GC) showed differences between the groups C and M18 at 7 days (P=0.013), and KC18 group showed smaller number of young fibroblasts (P=0.031) and collagen fibers (P=0.044) at 7 days. In immunohistochemical analysis, the CG showed significant difference between the M18 group and Groups C, M10 and KC (P=0.001) at 7 days, and between KC18 and the other groups (P=0.001) at 30 days. Macrophages were more expressive in the time period of 7 days in the Groups M18 and KC18, with significant differences with groups M, M10, KC, KC10 and control (P=0.001). TD test showed significant difference between all groups of Meron cement (P=0.001) and between Group KC with groups KC10 and KC18 (P=0.001). The CS test showed no significant difference between the cement Groups of Meron cement (P=0.385), but there was difference between the KC Group with KC10 and KC18 groups (P=0.001). The addition of chlorhexidine modified negatively the mechanical properties of diametral tensile strength, and compressive strength. The histocompatibility analysis showed that the intensity of histological changes in the cements with CX shown to be concentration-dependent, notably 18%. The Meron-CX-10% cement showed the best results of biocompatibility and Ketac-CX-18% more influence in the inflammatory process with a slower tissue repair.